Managing Agricultural Enterprises Exploring Profitability and Best Practice in Central Europe (Springer International Publishing, 2018)
Exploring the competitiveness and profitability of the agricultural sector in Central Europe, this book argues that the successful management of agricultural enterprises is inconceivable without the knowledge and application of modern forms of management and technology. Organised in an analytical framework and offering comprehensive empirical data, this book focusses on the countries of Poland, the Czech Republic, and Hungary. The contributors identify good practices, unresolved problems, and factors influencing profitability. Topics explored include the challenges of increasing sales potential, competitiveness, partnerships and cooperation, human resources issues, and risk management. By constituting a valuable source of knowledge, Managing Agricultural Enterprises is important to those researching the agricultural industry and management, but also to policy-makers and managers of agricultural enterprises.